A collaborative platform for an ambient assisted living ecosystem - Pereira, João Miguel de Almeida Clímaco (2018)
The population ageing is a global trend that affects almost all countries in the world. The global share of people with 60 years or over is expected to reach 21.6% by 2050. The social and economic impact of this tendency is huge, creating new challenges to healthcare and social support services. Furthermore, population ageing is linked to an increased number of people with physical limitations together with the isolation of persons. The Ambient Assisted Living paradigm seeks to answer to some of this challenges through the integration of innovative technologies, products, systems and services. Aiming the development of an ecosystem of products and services for Ambient Assisted Living, the AAL4ALL project was created joining more than thirty research, academic and industry partners. During the AAL4ALL project a 3-layered model of services ecosystem was adopted for the conceptual architecture. This work presents a collaborative platform as a contribution to the top layer of the conceptual architecture - AAL Ecosystem.